2002
DOI: 10.1046/j.1440-1614.2002.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Functioning in Children With DSM-IV Combined Type Attention Deficit Hyperactivity Disorder

Abstract: Children with combined type ADHD have mild to moderate global cognitive impairment together with some impairment of functions subserved by the frontal lobes. Longitudinal studies are required to determine if the deficit in global cognitive functioning is a primary deficit or secondary to the deficit in frontal lobe functioning. The importance of neuro-psychological assessment and follow-up for children with ADHD is stressed. Study limitations relate to the generalizability of the findings and the absence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 38 publications
2
24
0
1
Order By: Relevance
“…Moreover, children from both subtypes are characterized by poorer performances than their nondisordered peers on tests that measure academic skills [27,82]. Between them, subtype differences are minimal [29], although children with ADHD-IA perform more poorly on mathematics achievement tests [101][102][103].…”
Section: Intelligence and Achievement Testsmentioning
confidence: 99%
“…Moreover, children from both subtypes are characterized by poorer performances than their nondisordered peers on tests that measure academic skills [27,82]. Between them, subtype differences are minimal [29], although children with ADHD-IA perform more poorly on mathematics achievement tests [101][102][103].…”
Section: Intelligence and Achievement Testsmentioning
confidence: 99%
“…Executive function of the brain has a major role in daily life and achievements (5). Results of neuroimaging studies on children with ADHD were correlated with these clinical descriptions and revealed deficits in cerebellum and the frontal cortex of the brain, both of which have a fundamental role in planning, organization, decision making, time perception, inhibition, and thinking (6). Because of a complicated nature, these neurocognitive processes are neither included as diagnostic criteria nor as available treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Findings regarding working memory in ADHD are inconsistent (e.g., Stevens et al, 2002;Tripp et al, 2002;versus Barkley et al, 2001;Pennington and Ozonoff, 1996;Welsh, 2002). The most recent review of working memory in ADHD reveals growing evidence of deficits in the ability to maintain and manipulate visual-spatial information (Martinussen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%